An Analysis on Student Needs and Preferences for HyFlex Learning Development in Indonesian Higher Education - Panut Setiono; Punaji Setyosari; Henry Praherdhiono; Titik Harsiati; Yuli Amaliyah (CV. Media Inti Teknologi, 2025)
Background: The rapid advancement of digital technology has transformed higher education, leading to the development of HyFlex (Hybrid-Flexible) learning models that combine face-to-face, synchronous online, and asynchronous formats. However, research on students' technological readiness and preferences in HyFlex environments remains limited.Aims: This study examines students’ technological readiness, learning preferences, and access to digital resources in a HyFlex environment. It focuses on identifying commonly used devices, internet sources, preferred learning methods, activities, and resource types. The study’s novelty lies in its exploration of the intersection between mobile accessibility, learning formats, and resource types within HyFlex learning.Methods: A quantitative survey was conducted with 236 undergraduate students, and the collected data were analyzed using descriptive statistics to identify trends and patterns in technological readiness and learning preferences.Results: Findings show that most students use smartphones (41.1%) and mobile data (53.4%) to access learning materials. Blended learning was the preferred format (78.8%), with game-based and video-supported activities being highly favored. Additionally, 83.9% of students preferred online materials accessible via smartphones, emphasizing the importance of mobile-friendly resources in HyFlex learning.Conclusion: This study provides insights into optimizing HyFlex learning to better meet student needs. The findings suggest that HyFlex learning should prioritize mobile accessibility, interactive content, and flexible instructional design. This research contributes to the growing literature on flexible learning models and offers practical recommendations for designing future educational frameworks.